Early Bactericidal Activity of Delpazolid (LCB01-0371) in Patients with Pulmonary Tuberculosis - Kim, Ju Sang; Kim, Yong-hyun; Lee, Sang Haak; Kim, Yee Hyung; Kim, Jin-woo; Kang, Ji Young; Kim, Sung Kyoung; Kim, Seung Joon; Kang, Yun-Seong; Kim, Tae-hyung; Mok, Jeongha; Byun, Min Kwang; et al. (Antimicrobial agents and chemotherapy, 2022)
Delpazolid, an oxazolidinone, has been studied in non-clinical studies of efficacy and toxicity and Phase 1 clinical studies. Delpazolid has in vitro activity against Gram-positive bacteria, including Mycobacterium tuberculosis . Delpazolid, an oxazolidinone, has been studied in non-clinical studies of efficacy and toxicity and Phase 1 clinical studies. Delpazolid has in vitro activity against Gram-positive bacteria, including Mycobacterium tuberculosis . This study evaluated the bactericidal activity, safety, and pharmacokinetics of delpazolid in patients with pulmonary tuberculosis (TB). Seventy-nine subjects, aged 19 to 75 years with newly diagnosed smear-positive TB with no prior treatment for the current episode and no confirmed resistance to rifampin or isoniazid, were randomized to receive delpazolid 800 mg once a day (QD), 400 mg twice a day (BID), 800 mg BID or 1,200 mg QD or an active control of isoniazid, rifampin, pyrazinamide, and ethambutol (HRZE) or linezolid 600 mg BID. The primary endpoint was the average daily reduction in log transformed bacterial load, assessed on 7H11 solid-media culture, from days 0 to 14. The average daily decline in log-CFU was 0.044 ± 0.016, 0.053 ± 0.017, 0.043 ± 0.016, and 0.019 ± 0.017, for the delpazolid 800 mg QD, 400 mg BID, 800 mg BID, and the 1,200 mg QD groups, respectively. The average daily decline in log-CFU was 0.192 ± 0.028 for the HRZE group and 0.154 ± 0.023 for the linezolid 600 mg BID group. Three serious adverse events (SAE) were reported, one each in the delpazolid 400 mg BID group (death due to worsening of TB at day 2), the HRZE group (hospitalization due to pleural effusion) and the linezolid group (hyperkalemia); none of the SAEs were assessed as related to study drugs. This study has been registered at ClinicalTrials.gov with registration number NCT02836483.